Effects of grazing on grassland communities of the forest‐steppe of northern Mongolia: A comparison of grazed versus ungrazed places. (1st May 2018) - Takatsuki, Seiki; Sato, Masatoshi; Morinaga, Yuki
Abstract: Overgrazing of grasslands in the Mongolian steppes resulting from a transition from pastoral to sedentary livestock production has led to significant changes in plant communities. This study aimed to show how livestock grazing affects steppe vegetation in northern Mongolia by a good example of a long‐termed exclusion of grazing. The Bulgan Airport in northern Mongolia has been fenced since the 1950s and thus is suitable to compare grazed and ungrazed plant communities. We studied plots both inside and outside the fence with reference to community structure, species composition and growth form. Plant biomass for the outside plots averaged (40 g m −2 ) less than one‐seventh of that inside the fence (305 g m −2 ) and average species number per plot was about half of that inside the fence. Height of plants inside the fence ranged from the ground surface to 30–40 cm, whereas most of the plants outside were less than 10 cm tall. Erect, branched and tall tussock form plants were reduced outside the fence and short tussock and prostrate form plants became dominant. Microtopography resulted in different dominant plants inside the fence whereas only Carex duriuscula, a sedge and Potentilla acaulis, a short growing prostrate forb, prevailed outside. That is, grazing as a factor affecting plant communities prevailed and "masked" microtopography outside the fence. It was shown that the use of growth form is effective to evaluate vegetation changes by grazing.